Zonal Embedded Grids for LES of Self-Sustaining Structures of Wall Turbulence - 李玲 苑明顺 李全明 (Tsinghua science and technology, 2010)
In this study,a zonal grid refinement method based on the solution of weakly compressible flow equations with large eddy simulation in the finite volume method（FVM） and dynamic subgrid-scale model framework was used to simulate the turbulence structures of a plane-wall flow with Reynolds number Re=U0δ /ν =10 000.Comparison and analysis were conducted on the distributions of time-averaged velocity and velocity fluctuations,as well as on the actual near-wall structures,to verify the accuracy of the turbulence features that were simulated using the zonal grid refinement method.The results show that the zonal embedded grid is a very efficient way to illustrate the turbulence structures of the near-wall region.The present method is easy to implement and extend to small Mach number flow modeling on a collocated irregular FVM mesh system.